Iron, copper, magnesium and zinc status as pedictors of swimming performance - Lukaski, H. C.; Siders, W. A.; Hoverson, B. S.; Gallagher, S. K. (International Journal of Sports Medicine, 1996)
Human physical performance depends on many factors including skill, motivation, concentration, muscle mass, and nutritional components. Although the roles of water and carbohydrates are well established in promoting peak performance, there is limited information regarding the importance of the mineral elements in development of top levels of athletic performance. We studied a group of five female and five male collegiate swimmers and examined how well prediction equations, derived from another group of collegiate swimmers and based on estimates or iron, copper, magnesium, and zinc intake and blood biochemical measurements of nutritional status of these mineral elements, would relate to swim times measured during competition. We found no difference between 100-yd free-style times determined during championship competition and those predicted with the equations. This finding indicates the important, and previously unrecognized, role that trace element nutritional status plays in optimizing human physical performance. This information will be useful to dietitians and nutritionists who work with physically active people. It indicates that proper nutrition can be achieved by selecting nutritious foods and that nutritional supplements are not needed for optimal performance when a balanced diet is consumed.